The passions in play : Thyestes and the dynamics of Senecan drama - Schiesaro, Alessandro (Cambridge University Press, 2003)
This book subjects the most accomplished of Seneca's tragedies to a sustained critical analysis and argues for its central importance in post-Classical aesthetics. It also discusses several other of his plays, thereby offering a detailed and comprehensive analysis of the main themes and stylistic features of his tragedies.